(untitled) (Research, Society and Development, 2022)
Vegetarianism is a dietary pattern in which meat of animal origin is totally excluded, and which may present some classifications (ovo-lactovegetarian, lacto-vegetarian, ovo-vegetarian), depending on the inclusion of some foods of animal origin. Last years, interest in vegetarian diets associated with sports has increased significantly. Many athletes have been adhering to vegetarian food, generating discussion if this type of food provides the necessary nutrients, even more so when it comes to performance, since endurance athletes need a greater intake of macro and micronutrients. Therefore, the present study aimed to analyze the effect of a vegetarian diet on the performance of endurance sports practitioners. This is a narrative literature review, where articles published in the last 10 years (2011 to 2021) in PubMed, SciELO and Lilacs databases were analyzed. Studies show that through strategic selection and management of food choices, a properly planned vegetarian diet meets the energy, macro and micronutrient needs for good performance in endurance sports, as well as health as a whole. However, it is necessary to pay attention to the nutritional support of proteins, omega 3, vitamin B12, vitamin D, iron and calcium.